Tocilizumab improves clinical outcome in patients with active corticosteroid-resistant moderate-to-severe Graves’ orbitopathy: an observational study - Boutzios, Georgios; Chatzi, Sofia; Goules, Andreas V.; Mina, Areti; Charonis, George C.; Vlachoyiannopoulos, Panayiotis G.; Tzioufas, Athanasios G. (Frontiers in Endocrinology, 2023)
Background: Graves’ orbitopathy (GO) is an autoimmune disorder affecting the orbital fat and muscles. A significant role of IL-6 in the pathogenesis of GO has been described and tocilizumab (TCZ), an IL-6 inhibitor targeting IL-6R has been given in some patients. The aim of our case study was to evaluate the therapeutic outcome of TCZ in non-responders to first line treatments with corticosteroids. Methods: We conducted an observational study of patients with moderate to severe GO. Twelve patients received TCZ in intravenous infusions at a dose of 8mg/kg every 28 days for 4 months and followed up for additionally 6 weeks. The primary outcome was improvement in CAS by at least 2 points, 6 weeks after the last dose of TCZ. Secondary outcomes included CAS <3 (inactive disease) 6 weeks after TCZ last dose, reduced TSI levels, proptosis reduction by > 2mm and diplopia response. Results: The primary outcome, was achieved in all patients 6 weeks after treatment course. Furthermore all patients had inactive disease 6 weeks after treatment cessation. Treatment with TCZ reduced significantly median CAS by 3 units (p=0.002), TSI levels by 11.02 IU/L (p=0.006), Hertel score on the right eye by 2.3 mm (p=0.003), Hertel score on the left eye by 1.6 mm (p=0.002), while diplopia persisted in fewer patients (25%) after treatment with TCZ (not statistically significant, p=0.250). After treatment with TCZ, there was a radiological improvement in 75% of patients, while 16.7% showed no response, and in 8.3% of patients deterioration was established. Conclusion: Tocilizumab appears to be a safe and cost effective therapeutic option for patients with active, corticosteroid-resistant, moderate to severe Graves’ orbitopathy.